Pengaruh Pertumbuhan Perusahaan Terhadap Nilai Perusahaan dengan Kinerja Keuangan Sebagai Variabel Mediasi pada Perusahaan Pertambangan yang Terdaftar di Bursa Efek Indonesia Periode 2019-2023 - Dwi Indra Agustino; Siti Sundari (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This study aims to examine and analyze the effect of company growth on firm value with financial performance as a mediating variable. This research employs a quantitative method using secondary data in the form of annual financial statements obtained from the official website of the Indonesia Stock Exchange (IDX) and the official websites of mining sector companies. The population in this study consists of mining sector companies listed on the Indonesia Stock Exchange for the period 2019–2023, totaling 81 companies, with a sample of 15 companies. The data analysis technique used is Partial Least Squares (PLS) with the assistance of SmartPLS software. The results of the study indicate that company growth has a significant effect on firm value and also has a significant effect on firm value through financial performance. These findings suggest that financial performance plays a mediating role in strengthening the relationship between company growth and firm value.